Nurses' understanding and experience of applying painful stimuli when assessing components of the Glasgow Coma Scale. Issue 21 (5th September 2019) - Cook, Neal F.; Braine, Mary E.; Trout, Ruth
Abstract: Aims and objectives: To evaluate nurses' application, understanding and experience of applying painful stimuli when assessing components of the Glasgow Coma Scale. Background: The Glasgow Coma Scale has been subjected to much scrutiny and debate since its publication in 1974. However, criticism, confusion and misunderstandings in relation to the use of painful stimuli and its application remain. An absence of evidence‐informed guidance on the use and duration of application of painful stimuli remains, with the potential to negatively impact on decision‐making, delay responsiveness to neurological deterioration and result in adverse incidents. Design and Methods: This international study used an online self‐reported survey design to ascertain neuroscience nurses' perceptions and experiences around the application of painful stimuli as part of a GCS assessment ( n  = 273). The STROBE checklist was used. Results: Data revealed varied practices and a sense of confusion from participants. Anatomical sites for the assessment of pain varied, but most respondents identified the trapezius grip/pinch in assessing eye‐opening and motor responses. Most respondents identified they assess eye‐opening and motor responses together and apply pain for <6 s to elicit a response. Witnessed complications secondary to applying a painful stimulus were varied and of concern. Conclusion: Neuroscience nurses in this study clearly required evidence‐informed guidelines to underpin practice both in applying painful stimuli and in managing the experience of the person in their care and the family response. A standardised approach to education is necessary to ensure greater interrater reliability of assessment not only within nursing but across professions. Relevance to practice: Results of this study illustrate inconsistency and confusion when using the Glasgow Coma Scale in practice; this has the potential to compromise care. Clarity around the issues highlighted is necessary. Moreover, these results can inform future guidelines and education required for supporting nurses in practice.